Description of Craftsmen's Creativities in Developing Sulaman Bayangan Crafts in Nagari Barung-Barung Balantai - Sari, Tila Maya; Solfema, Solfema (SAINTIS Publishing, 2019)
This study was motivated by the success of the Sulaman Bayangan crafts activities in Nagari Barung-Barung Balantai, this was allegedly because the craftsmen had a creative personality. This study aims to see the picture of the creativity of Sulaman Bayangan crafts in Nagari Barung-Barung Balantai viewed from the aspect of having curiosity, confidence, and risk-taking. This type of study is a quantitative descriptive study. The population in this study were Sulaman Bayangan crafts totaling 70 people. The sampling method is proportionate stratified random sampling, the sample taken is 35 people. The technique of collecting data uses a questionnaire. While the data collection tool is a questionnaire. The data analysis technique uses the percentage formula. The results showed that (1) the level of craftsman creativity in the aspect of having curiosity was said to be high, (2) the level of craftsman creativity in the aspect of trust was said to be high, (3) the level of creativity the craftsmen in the aspect of taking risks was said to be high.